Cancer prevention in Africa: liver cancer - Ndom, Paul (Ecancermedicalscience, 2019)
Hepatocellular carcinoma is a common cancer in Africa. The risk factors are well known and avoidable in most cases (hepatitis B, hepatitis C, aflatoxin and alcohol). Vaccination against hepatitis B and the fight against aflatoxin are efficient contributions to the fight against liver cancer. The costly nature of these measures in Africa is an impediment to the fight against liver cancer in Africa.